Professors in Humanities at Vilnius University and the Doctrine in the Period of Activities of Donatas Sauka - Lukšaitė, Ingė (Literatūra, 2020)
The analysis of professors in Humanities at Vilnius University in 1948–1956, the period of studies and post-graduate course of Donatas Sauka, established that professors who had not accepted the doctrine of Marxism-Leninism and who had obtained their academic titles in independent Lithuania or pre-revolutionary Russia had left the university. During the first year of Soviet rule, a group of persons who had contributed to Lithuania’s incorporation into the USSR and undertaken to establish the doctrine at the university became professors. They were active in the 1940s and 1950s and created a climate of fear. Some lecturers who were neutral towards the doctrine had been granted the title of professors for their contribution to the science in order to raise the prestige of the university. A cluster of lecturers who attempted to interpret literature without applying primitive sociologisation was formed in the Department of Lithuanian Literature in mid 1950s. At the initiative of the Central Committee of the Lithuanian Communist Party, actions were taken (1956–1961) to force the group of young lecturers to follow the requirements of the doctrine. Having defied the requirements, they were dismissed. D. Sauka belonged to the group, but had retained his job as a lecturer without changing his views towards the doctrine. Some professors, associate professors, and students at the university participated in the ideological cleansing of the Department of Lithuanian Literature. They were later promoted. During the 1960s, among literary scholars only Jurgis Lebedys became a professor. At that time, high qualification requirements for obtaining a professor’s title were set in the USSR. Those who had obtained the titles of professors had different approaches towards the doctrine of Marxism-Leninism. Some showed support only formally and expanded the scope of analysed issues by slowly validating new fields of knowledge and developed individual thinking; others attained high qualification and performed the actions of implementing the doctrine required by the party leaders; still others sought their personal goals by using maintenance of the doctrine as a pretext. The guardians of the doctrine created obstacles for unwanted persons in becoming professors by trying to prevent them from defending their doctoral (post-doctoral) theses and publishing their articles and works; they tried to create a wall of silence around them. In the 1970s, D. Sauka and Vytautas Kubilius defended their doctoral (post-doctoral) theses; both of them had surpassed the topics defined by the doctrine and opened new fields of knowledge in Lithuanian literature and culture. Attempts were made to prevent them from defending their theses, but thanks to the vigilance of his colleagues, D. Sauka defended his thesis and became a professor after four years. The approval of V. Kubilius’s doctoral (post-doctoral) title lasted six years, yet one of the strongest literary critics and scholars was not granted the title of professor from the Soviet university. In the 1980s, a number of students at Vilnius University obtained titles of professors. The doctrine itself had changed at that time, the communist government avoided scandals, the level of mentality was higher at the university, and simultaneously, the behaviour of lecturers themselves was self-censored; some of the guardians of the doctrine had voluntarily abandoned their position and those who appreciated the works of their talented colleagues appeared. At the juncture of the 1980s and 1990s, professors of Vilnius University became more prominent in the society: these were personalities that developed individual thinking of their own and others, done valuable work for the culture of Lithuania, retained relations with the nation and had the goal of creating an independent state of Lithuania.
Keywords: Doctrine; Marxism-Leninism; intellectual environment; Vilnius University; professorship; individual self-sufficiency; creativity